Sub-representação feminina em partidos políticos em Goiás - Silva, Gabriela Peixoto Vieira (2014)
This work purpose to investigate the female participation in leading positions on political parties. The hypothesis that guides the research is that this participation is low, corroborating the existence of a under representation of women in leading positions on the analyzed political parties. This under representation is analyzed on two directions: the function/position in the party which identify or not the inclusion of women in the elite party and the identification of elements that shape this participation. The research is divided in two different parts one is documental, which it will be approached positions occupied by women, and finally the analysis of the interviews with male and female leadership from the parties analysed: PMDB, PSDB, DEM, PT and PCdoB.